Financial Impacts of Liver Fluke on Livestock Farms Under Climate Change–A Farm Level Assessment - Shrestha, Shailesh; Barratt, Alyson; Fox, Naomi J.; Vosough Ahmadi, Bouda; Hutchings, Mike R. (Frontiers in Veterinary Science, 2020)
Liver fluke infection (fascioliasis) is a parasitic disease which affects the health and welfare of ruminants. It is a concern for the livestock industry and is considered as a growing threat to the industry because changing climatic conditions are projected to be more favourable to increased frequency and intensity of liver fluke outbreaks. Recent reports highlighted that the incidence and geographic range of liver fluke has increased in the UK over the last decade and estimated to increase the average risk of liver fluke in the UK due to increasing temperature and rainfall. This paper explores financial impacts of the disease with and without climate change effects on Scottish livestock farms using a farm-level economic model. The model is based on farming system analysis and uses linear programming technique to maximise farm net profit within farm resources. Farm level data from a sample of 160 Scottish livestock farms is used under a no disease baseline scenario and two disease scenarios (with and without climate change). These two disease scenarios are compared with the baseline scenario to estimate the financial impact of the disease at farm levels. The results suggest a 12% reduction in net profit on an average dairy farm compared to 6% reduction on an average beef farm under standard disease conditions. The losses increase by two folds on a dairy farm and six folds on a beef farm when climate change effects are included with disease conditions on farms. There is a large variability within farm groups with farms with higher profitability incurring relatively lesser economic losses than farms with lower profitability. There is a substantial increase in number of vulnerable farms both in dairy (+20%) and beef farms (+27%) under the disease alongside climate change conditions.